Ramp Lesions of the Posterior Segment of the Medial Meniscus: What Is Repaired? A Qualitative Histological Study of the Meniscocapsular and Meniscotibial Attachments. Issue 12 (December 2020) - Di Francia, Rémi; Nicolas, Quentin; Quintin-Roué, Isabelle; Le Henaff, Goulven; Gunepin, François-Xavier; Dubrana, Frédéric
Abstract: Background: Lesions of the posterior segment of the medial meniscus are the most common intraarticular lesions associated with ACL injuries. Ramp lesions are tears in the peripheral attachment of the posterior horn of the medial meniscus. Such injuries are difficult to detect on preoperative MRI. Arthroscopically, the prevalence of these lesions can reach 24%. Anatomical descriptions of the posterior horn of the medial meniscus are becoming clearer, however, histological descriptions are lacking, especially with regard to the presence or absence of capillaries. Questions/purposes: The present qualitative histologic study focused on the posterior segment of the medial meniscus and the meniscocapsular and meniscotibial junctions. Specifically, the objective of this study was to analyze the posterior segment of the medial meniscus and the meniscosynovial junction and to determine whether the meniscus tibial ligament exists. Methods: We dissected 10 unpaired cadaveric knees (five male, five female, age range 55 to 66 years), five left and five right, from the French "Don du corps" body donation program via a posterior approach to the posteromedial capsule. We excluded specimens with intra-articular abnormalities (ACL rupture, meniscal tear, arthrosis) preceding dissection by arthrotomy. We thus accessed the posterior segment of the medial meniscus and the meniscosynovial junction. The proximal capsule, posterior segment of the medial meniscus, entire meniscal capsular-tibial junction, and a fragment of the tibia were removed en bloc. For each knee, three sagittal spaced sections of the posterior segment of the medial meniscus (Zone 4 as defined by Śmigielski) were performed. Two experienced pathologists performed qualitative histological analysis on the 30 samples after Hematoxylin and eosin staining, and Safranin O staining. Results: Macroscopically, the meniscotibial attachments were pellucid and homogeneous, as were the meniscocapsular attachments; however, the meniscocapsular attachments appeared to be denser in both the anterior and posterior regions of the capsule. Microscopy of the meniscosynovial junction revealed loose collagen fibers that were partially oriented but not parallel, a cellular network featuring a few fibroblasts and adipocytes, and several capillaries. No between-attachment histologic differences were apparent; both tissues shared a site of attachment to the posterior horn of the medial meniscus. We did not detect the meniscotibial ligament, macroscopically or microscopically. Conclusions: A ramp lesion may not be a ligamentous injury because the meniscotibial ligament was not detected. Rather, it appears that a ramp lesion is a tear in the common attachment point between the posterior horn of the medial meniscus and meniscocapsular and meniscotibial junctions. This structure is vascularized, and contains nonoriented low cellularity collagen of moderate density. Clinical Relevance: Based on our results, a better rationale for the recommendation of surgical repair of a ramp appears to be needed, given the absence of a meniscotibial ligament, and the presence of capillaries in the meniscocapsular and meniscotibial attachments.